EVALUATION OF LAND CONSOLIDATION WORKS IN TERMS OF LEGAL RESULTS: THE CASE OF ADANA PROVINCE, TURKIYE - Ahmet MERT; Şinasi AKDEMIR; Derviş ÖNEN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Land consolidation is the rearrangement of small, fragmented, and scattered land owned by agricultural enterprises. The data of the research was collected from the lawsuit files related to the land consolidation works carried out in Yüreğir district of Adana province on 23/11/2012, records of the 6th Regional Directorate of State Hydraulic Works (DSI) which carried out the consolidation and academic studies related to the subject. It is aimed to use less time, labour, and capital, increase agricultural production and productivity, and raise living standards. However, it is important to ensure satisfaction of farmers to provide these benefits. This study evaluated the problems caused by land consolidation from a legal point of view. This research found that the number of parcels of enterprises decreased, the size of the parcels increased, and the parcels received road, water, and drainage services. However, a significant number of producers were not satisfied with the land consolidation and filed lawsuits in the administrative courts. This study revealed that attentive consolidation and careful use of authority can increase satisfaction and prevent unnecessary busying of the courts, saving time and expense.